Living through crisis by Lake Chad: violence, labor and resources - Iocchi, Alessio (Routledge studies in peace, conflict and security in Africa, 2023)
"This book investigates the ways in which people in the Lake Chad region that divides Nigeria, Niger, Chad, and Cameroon deal with the crises of violence, jihadism, drought, and climate change that continue to afflict the area. In 2014 Boko Haram expanded into the Lake Chad region, prompting a counter-insurgency response, and exacerbating pre-existing social and ecological challenges. Drawing on extensive ethnographic research, this book investigates how people within the liminal space of this key border region respond to and navigate the unpredictability which typifies their day-to-day lives. Building up a picture of individual and community experiences of crisis, the book gradually demonstrates the complex interactions between economic circuits, political orders, socio-religious processes, and labour practices which operate in the region. This book will be of interest to researchers across African studies, security studies, political science, and border studies"--